OPTIMASI ANALISIS TEKNIKAL DALAM STRATEGI PEMASARAN MINYAK KELAPA SAWIT: MODEL PERAMALAN HARGA HARIAN UNTUK 30 HARI TRANSAKSI - Ambar Kurniawan; Ahmad Haslan Saragih (Pusat Penelitian Kelapa Sawit, 2017)
Information on future trends in price movement has a strategic role in the palm oil business. Through this information then embodied in the form of product marketing strategy. This study aims to build a daily price forecasting model for 30 days of forward transactions (Model 30 DTH) and based on the technical analysis. Goodness of fit is based on the suitability of the trend of price movement and the daily margin error between the forecast and the actual price in the future (ex-ante). Referring to both indicators from the Formulation stage to the 9th Validation, it shows that the model is relatively good in predicting daily price movement trends as well as daily error margins.